The Analysis of Biomechanical Properties of Proximal Femur after Implant Removal - Jae Hyuk Yang; Tae Gon Jung; Arjun Rupanagudi Honnurappa; Jae Min Cha; Chang Hwa Ham; Tae Yoon Kim; Seung Woo Suh (Applied Bionics and Biomechanics)
Introduction. To compare the biomechanical stability of the femur following the removal of proximal femoral nail antirotation (PFNA-II) and dynamic hip screw (DHS). Material and Methods. 56 paired cadaveric femurs were used as experimental and control groups. In the experimental group, PFNA-II and DHS were randomly inserted into femurs on both sides and then removed. Thereafter, compression load was applied until fracture occurred; biomechanical stability of the femurs and associated fracture patterns were studied. Results. The ultimate load and stiffness of the control group were 6227.8±1694.1 N and 990.5±99.8 N/mm, respectively. These were significantly higher than experimental group (p=0.014, <0.001) following the removal of PFNA-II (4085.6±1628.03 N and 656.3±155.3 N/mm) and DHS (4001.9±1588.3 N and 656.3±155.3 N/mm). No statistical differences in these values were found between the 2 device groups (p=0.84, 0.71), regardless of age groups. However, fracture patterns were different between two devices, intertrochanteric and subtrochanteric fractures. Conclusions. Mechanical stability of the proximal femurs does not differ after the removal of 2 different of fixation devices regardless of the age. However, it was significantly lower compared to an intact femur. Different fracture patterns have been shown following the removal of different fixation devices as there are variations in the site of stress risers for individual implants.